PERBANDINGAN TEKNIS DAN EKONOMIS SANDBLASTING MENGGUNAKAN METODE PASIR SILIKA DAN STEEL GRIT - Nur Avia Safitri (2022)
Sandblasting process is a working process in which the surface of the hull is made rough according to the standards used by firing abrasive material to the surface of the plate with a certain pressure. This activity is usually carried out at the end of the ship repair process. Usually this process is carried out before carrying out the painting process, because the final result of this process is very influential during the painting process, so that the paint can adhere and not easily peel off. In general, the abrasives used in the sandblasting process are silica sand and steel grit. This study aims to compare the implementation and cost of the sandblasting process using the silica sand and steel grit methods. The author hopes that the selection of a good and economical method for the implementation of the sandblasting process. The results of this study can be seen that in the sandblasting process there is an abrasive standard that is used according to the needs of the ship. The difference in the price of silica sand in the market and the difference in the cost of labor wages are raised. The comparison of silica sand and steel grit can be distinguished, technically the sandblasting process using silica sand and steel grit is the same but there are differences in tools, productivity and total processing time. And economically the use of silica sand is better than steel grit because the price of silica sand is cheaper than steel grit. And silica sand is a recommendation for the use of abrasive materials in the sandblasting process in ship repair.